ANALISIS KESULITAN PEMBELAJARAN AL QURAN BAGI IBU-IBU PESERTA MAJELIS TAKLIM AL HIKMAH DI KOMPLEK DDN II PONDOK LABU CILANDAK JAKARTA SELATAN: ANALYSIS OF DIFFICULTIES IN LEARNING THE QURAN - Aziz, Abdul; Zakiyah , Siti; anam, khairul; Fauzan, Asep (LP2M JAMIAT KHEIR, 2025)
This study aims to analyze the various difficulties experienced by mothers participating in the Al-Hikmah Islamic study group (Majelis Taklim Al-Hikmah) at the DDN II Pondok Labu Complex, Cilandak, South Jakarta, in learning the Quran. The study used a qualitative approach through in-depth interviews with five participants with diverse ages, educational backgrounds, and learning experiences. The results showed that the main difficulties included technical issues such as mastery of the rules of makhraj and tajweed, limited reading fluency, and mispronunciation of certain letters. Furthermore, age, cognitive decline, visual and hearing impairments, and lack of study time were significant obstacles. Difficulties also arose due to the lack of competent teacher support and the lack of learning methods appropriate to the characteristics of adult learners. The findings of this study emphasize the importance of more adaptive, systematic, and personalized Quran learning strategies to accommodate the needs and conditions of the mothers participating in the Islamic study group.